2015
DOI: 10.1155/2015/256028
|View full text |Cite
|
Sign up to set email alerts
|

First Report ofKlebsiella pneumoniae-Carbapenemase-3-ProducingEscherichia coliST479 in Poland

Abstract: An increase in the antibiotic resistance among members of the Enterobacteriaceae family has been observed worldwide. Multidrug-resistant Gram-negative rods are increasingly reported. The treatment of infections caused by Escherichia coli and other Enterobacteriaceae has become an important clinical problem associated with reduced therapeutic possibilities. Antimicrobial carbapenems are considered the last line of defense against multidrug-resistant Gram-negative bacteria. Unfortunately, an increase of carbapen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Tigecycline seems to be used in infections caused by many MDR strains, for example ESBL-positive phenotype strains [3,6,14]. In our study, tigecycline demonstrated the highest in vitro sensitivity to K. pneumoniae, even to ESBL+ and E. coli strains, a phenomenon which is confirmed by other authors [16,[18][19][20]. For E. cloacae, other authors have shown the high in vitro activity of tigecycline [19], which was an opposite result to the one in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Tigecycline seems to be used in infections caused by many MDR strains, for example ESBL-positive phenotype strains [3,6,14]. In our study, tigecycline demonstrated the highest in vitro sensitivity to K. pneumoniae, even to ESBL+ and E. coli strains, a phenomenon which is confirmed by other authors [16,[18][19][20]. For E. cloacae, other authors have shown the high in vitro activity of tigecycline [19], which was an opposite result to the one in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The enormous genome plasticity of Gram-negative bacteria enables the accumulation of many different mechanisms of resistance to various antimicrobial agents. As a result, the increased emergence of MDR or XDR pathogens considerably reduces the opportunities for effective treatments against these bacteria (Livermore et al, 2011;Ojdana et al, 2015). A number of recent reports highlights the importance of mcr dissemination in clinical MDR bacteria, especially among subpopulations of pathogens persisting in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results indicated carbapenem resistance mediated by β-lactamase production among the second strain isolated from the urine sample. The tested strains were analyzed for the presence of resistance mechanisms against β-lactam antibiotics using polymerase chain reaction (PCR) amplifications for β-lactamase genes (bla TEM , bla SHV , bla CTX-M ) and for bla genes responsible for carbapenemase production (bla VIM , bla IMP , bla NDM , bla KPC , bla OXA-48 ) with the use of primers as described previously (Ojdana et al 2015). The results of PCRs and sequencing are presented in Table 1.…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…Over the last years, carbapenemase-producing K. pneumoniae (CPKP) strains have been detected not only among hospitalized patients but also among residents of longterm care facilities (Saegeman et al 2015). Our analyses indicated a significant degree of spread among microorganisms with resistance mechanisms against antibiotics such as ESBLs or even KPC enzymes (Ojdana et al 2015). Considering the acquisition of a strain from the hospital environment, we determined the genetic relationship of isolated strains using the PFGE method.…”
Section: Pfge Pulsotypementioning
confidence: 99%